Symbolic Tree Automata - Veanes, Margus; Bjørner, Nikolaj (Information Processing Letters, 2015)
We introduce symbolic tree automata as a generalization of finite tree automata with a parametric alphabet over any given background theory. We show that symbolic tree automata are closed under Boolean operations, and that the operations are effectively uniform in the given alphabet theory. This generalizes the corresponding classical properties known for finite tree automata.